Infographics: Representation of reality, Advertising and Organizational Communication - Karbaum Padilla, Gerardo (2015)
Human communication is the process which allows the human being to evolve as specie in an unfavorable world. Humanity found images, followed then by words, considered both as powerful tools that help to deliver information generation after generation. Sum of them provided the creation of infographies or information graphics, a very important application in the journalist field. However, they are very well used on fields such as advertising and organizational communications; this work tries to offer new options applying the infographic discipline but also to understand as a very efficient and decisiveway to represents our reality.